‘What Else About Her Is Fake?’: ‘Emphasised’ Femininity, Authenticity and Appearance - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
This chapter charts the ways in which young women’s negotiations of dress in the NTE are shaped by notions of visibility and authenticity and also by class. I explore the ways in which an exaggerated or emphasised mode of femininity is normalised to an extent within the NTE and highlight some of the pleasures and values young women found in their negotiations of femininity through dress, whether wholeheartedly embracing or ‘flashing’ femininity. Tensions and ambivalences are exposed as the participants both adopted and resisted elements of ‘girly’ and ‘tomboy’ identities. I then explore the ways in which forms of classed othering function to construct the feminine self in contrast to those who are perceived to lack the taste and resources to ‘do’ femininity appropriately and instead embody a somehow inauthentic and overdone performance of femininity. I briefly consider the intersections between hyper-feminine and ‘slutty’ dress, and finally explore how attempts by working-class young women to resignify a more excessive look as ‘glamorous’ may be mocked and judged beyond the local context.
Keywords: Essex Girl; Geordie; Girly Girl; Tomboy; clothingClothing